Green sustainable process for chemical and environmental engineering and science : analytical techniques for environmental and industrial analysis - Inamuddin, 1980-; Boddula, Rajender; Asiri, Abdullah M. (Elsevier, 2021)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Analytical Techniques for Environmental and Industrial Analysis offers an in-depth overview of analytical tools used in the analysis of environmental and industrial samples. The basic related to the qualitative and quantitative analysis and challenges responsible for analytical methods of analysis are discussed in detail. It also summarizes the spectroscopic tools to study the environmental and industrial samples. It reviews all-types of green analytical tools and methods used for the analysis of soil and sediment, wastewater, toxic organic and inorganic analytes, and biological samples. The analytical methods for the analytes of industrial importance like pharmaceutical industries, food industries, metal, water, and cement industries are discussed. This book provides an overview of the environmental and industrial analysis using green analytical chemistry tools and methodologies usable in environmental, analytical, engineering, pharmaceutical, and industrial sectors.